Necrotic lower extremities ulcers caused by calciphylaxis in chronic renal failure patient - Nyoman Suryawati; Herman Saputra (DiscoverSys Inc, 2018)
Introduction: Lower extremity ulcers often create diagnostic challenges and influence patient morbidity and mortality. The most common causes are venous insufficiency, arterial insufficiency, and neuropathic. Ulcers associated with systemic condition often face diagnostic and therapeutic challenge. We report a necrotic lower extremity ulcer caused by calciphylaxis in a patient with chronic renal failure.Â Case: We reported a 48-year-old Javanese woman, complained of painful lower extremities ulcers since 1.5 months ago. The patient had a history of renal failure and hypertension, undergone routine hemodialysis since 13 years ago, and used Continuous Ambulatory Peritoneal Dialysis (CAPD) since one year ago. Dermatology status on dorsum pedis sinister as well as cruris dexter and sinister showed multiple ulcers on livid skin covered by black eschar, accompanied by tenderness. Laboratory results showed anemia (Hb 7.6), hypoalbuminemia (2.7), increased serum urea level (170.4 mg/dl), increased serum creatinine (11.23 mg/dl), increased calcium (10.4 mg/dl), high inorganic phosphorus (8.5 mg/dl) and high parathyroid hormone (2,164). BOF examination showed abdominal calcification, while radiographic examination on cruris dexter et sinister showed soft tissue calcification and osteoporosis. Histopathology result supported the presence of calciphylaxis. The patient was diagnosed with stage V chronic renal failure, hypertension, and calciphylaxis caused by secondary hyperparathyroidism. She was managed by low calcium and phosphate diet, lanthanum, paracetamol, folic acid, adalat oros, captopril and wound debridement.Â Conclusion: Calciphylaxis is a rare phenomenon of cutaneous necrosis associated with end-stage renal disease. Control of end-stage renal disease may be an important factor for treatment of calciphylaxis and patient with calciphylaxis usually had a poor prognosis.Keywords: necrotic lower extremity ulcer, chronic renal failure, calciphylaxis